Estimating of Critical Gaps at Uncontrolled Intersections under Heterogeneous Traffic Conditions - Al Bargi, Walid Abdullah; Rohani, Munzilah Md; Daniel, Basil David; Khalifaa, Nasradeen A; Masirin, Mohd Idrus Mohd; Kironde, Joel (Automotive Experiences, 2023)
Pedestrian crossing behavior can be studied by estimating critical gap, which is determined by analyzing accepted and rejected gaps by pedestrians. This can provide insight into safety levels at pedestrian facilities. The aim of this study is to determine critical gaps using various methods such as the Logit method, Raff's method, and Wu’s Method. These methods are then compared to identify the most appropriate one. Three locations in Malaysia were selected for data collection based on their land use, number of lanes, and carriageway width. Video cameras were used to capture mixed traffic flow and pedestrian crossing movements simultaneously at the selected sections. The results indicate that the critical gap values obtained from the three methods are highly comparable. Specifically, the Logit Method yielded a critical gap value of 8.4s, while Raff's Method and Wu's Method produced critical gap values of 7.7s and 7.12s, respectively. The study concludes that the Logit method is the most suitable for estimating critical gaps as it takes into account both pedestrian behavior and vehicular characteristics concurrently. The findings of this study have the potential to contribute to the review of design parameters for pedestrian crossing facilities, leading to the improvement of existing facilities and the enhancement of pedestrian safety.